Regulation of Lymphatic GM-CSF Expression by the E3 Ubiquitin Ligase Cbl-b - Peer, Sebastian; Cappellano, Giuseppe; Hermann-Kleiter, Natascha; Albrecht-Schgoer, Karin; Hinterleitner, Reinhard; Baier, Gottfried; Gruber, Thomas (Frontiers in Immunology, 2018)
Genome-wide association studies as well as lymphatic expression analyses have linked both Cbl-b and GM-CSF to human multiple sclerosis as well as other autoimmune diseases. Both Cbl-b and GM-CSF have been shown to play a prominent role in the development of murine encephalomyelitis; however, no functional connection between the two has yet been established. In this study, we show that Cbl-b knockout mice demonstrated significantly exacerbated severity of experimental autoimmune encephalomyelitis (EAE), augmented T cell infiltration into the central nervous system (CNS) and strongly increased production of GM-CSF in T cells in vitro and in vivo. GM-CSF neutralization demonstrated that the increased susceptibility of Cbl-b deficient mice to EAE was dependent on GM-CSF. Mechanistically, p50 binding to the GM-CSF promoter and the IL-3/GM-CSF enhancer element “CNSa” was strongly increased in nuclear extracts from Cbl-b-deficient T cells. This study suggests that Cbl-b limits autoimmunity by preventing the pathogenic effects of GM-CSF overproduction in T cells.